Sub-Seafloor Replacement Mineralization: Lessons From The Neves Corvo VHMS Deposit - Jorge MRS Relvas (International Marine Minerals Society, 2011)
Recent research both on active and fossil systems has demonstrated that shallow subseafloor replacement processes are not only viable depositional mechanisms for massive sulfide mineralization, but likely contributed as a major component of the mineralization occurring in large VHMS deposits and in many present-day seafloor hydrothermal systems. In the giant Neves Corvo deposit, as in many others VHMS deposits of the Iberian Pyrite Belt, there is overwhelming evidence for silicate-sulfide replacement processes being largely responsible for the efficiency of the ore-forming systems and huge size of the deposits. Textural evidences at all scales, coupled with a well-constrained mass-balance geochemical analysis, indicate that extensive replacement in the lavadominated volcanic rocks of the footwall sequence, and disseminated replacement mineralization in the volcaniclastic and/or sedimentary units were major mechanisms of ore formation in the Neves Corvo deposit. Shallow metal deposition prior to fluid discharge on the seafloor is likely to play a major role in seafloor massive sulfide mineralization. This premise should be envisaged as critical in evaluating the economic potential of seafloor resources, and should certainly be part of the equation when plans for seafloor mineral exploration missions are drawn.